2024
DOI: 10.1002/cnr2.1941
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of reinforcing sutures for prevention of anastomotic leakage after low anterior resection for rectal cancer: A systematic review and meta‐analysis

Shuanhu Wang,
Yi Zhang,
Song Tao
et al.

Abstract: Background and ObjectivesAnastomotic leakage is a serious complication following surgery for cancer of the rectum. It is not clear whether reinforcing sutures could prevent anastomotic leakage. Therefore, this study aims at evaluating the efficacy of reinforcing sutures on anastomotic leakage.MethodsWe searched PubMed, Embase, and the Cochrane Library databases from inception to January 31, 2023. We included studies comparing anastomosis with reinforcing sutures to anastomosis without reinforcing sutures after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…A recent systematic review and meta-analysis by Wang et al demonstrated a lower incidence of anastomosis leakage (RR 0.41, 95% CI 0.25-0.66) in patients with reinforcing sutures with a leakage rate of 4.4% compared to the 11.9% for whom no reinforce suture was performed. [10] Our data align with the existing literature that compares SPRS with single-incision laparoscopic surgery (SILS), showing comparable operation times [6,7]. Our mean operation time of 222.4min is longer than that reported by Change et al (185min) but shorter than the comparative analysis performed by Keller et al (296min).…”
Section: Discussionsupporting
confidence: 89%
“…A recent systematic review and meta-analysis by Wang et al demonstrated a lower incidence of anastomosis leakage (RR 0.41, 95% CI 0.25-0.66) in patients with reinforcing sutures with a leakage rate of 4.4% compared to the 11.9% for whom no reinforce suture was performed. [10] Our data align with the existing literature that compares SPRS with single-incision laparoscopic surgery (SILS), showing comparable operation times [6,7]. Our mean operation time of 222.4min is longer than that reported by Change et al (185min) but shorter than the comparative analysis performed by Keller et al (296min).…”
Section: Discussionsupporting
confidence: 89%
“…However, intracorporeal reinforcing suturing of the anastomosis using the robotic system can reduce the possible occurrence of anastomosis leakage. A recent systematic review and meta-analysis by Wang et al demonstrated a lower incidence of anastomosis leakage (RR 0.41, 95% CI 0.25-0.66) in patients with reinforcing sutures, with a leakage rate of 4.4% compared to the 11.9% for whom no reinforcing suture was performed [14].…”
Section: Discussionmentioning
confidence: 99%